Language Variation and Change? Gender Agreement in Franco-American Descriptive Adjectives - Fox, Cynthia A.; Stelling, Louis E. (Canadian Journal of Applied Linguistics, 2014)
Abstract Studies of Franco-American French (FAF) suggest that this obsolescing variety spoken in the northeastern United States is resistant to grammatical changes that are typical in situations of language contact, restriction, and shift. Here we address the issue through an examination of gender agreement in descriptive adjectives. Our analysis of data from four communities shows that a tendency toward morphological reduction in the direction of the masculine variant that has been widely documented in the popular French of France and in many North American varieties is widespread in terms of number of speakers that exhibit this behaviour, but infrequent overall. Variation is conditioned by the nature of the final segment and by speaker community of residence and education in French. We relate these factors to widespread negative attitudes about FAF that have contributed to a community-wide shift to English on the one hand and to grammatical conservatism among speakers who have maintained French on the other. Résumé Les études effectuées sur le français franco-américain (FFA) suggèrent que cette variété résiste aux changements grammaticaux qui sont typiques des situations de contact de langues et de transfert linguistique. Ici, nous abordons la question par un examen de la variabilité dans l’accord des adjectifs descriptifs. Notre analyse des données d’entrevues sociolinguistiques auprès de locuteurs habitant quatre villes dans le nord-est des États-Unis montre qu’une tendance vers la réduction morphologique dans la direction de la variante masculine qui a été largement documentée dans le français populaire de France et dans de nombreuses variétés du français nord-américain est répandue pour ce qui est du nombre de locuteurs qui la manifeste, mais peu fréquente. La variation est conditionnée par la nature du segment final, par la communauté de résidence et par l’éducation en français des locuteurs. Nous relions ces facteurs aux attitudes négatives au sujet du FFA qui ont contribué au transfert à l’anglais à l’échelle de la communauté d’une part, et au conservatisme linguistique parmi ceux qui ont maintenu le français de l’autre.